This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Solution "without using Calculus" : Let's denote S k = ∑ n = 1 ∞ 2 n n k (see the remark at the end of the solution) . Since S 0 is the sum of a geometric series whose first term is 2 1 and ratio 2 1 , then S 0 = 2 1 1 − 2 1 1 = 1 . Now, we can see that S 1 = n = 1 ∑ ∞ 2 n n = 2 1 + n = 2 ∑ ∞ 2 n n = 2 1 + n = 1 ∑ ∞ 2 n + 1 n + 1 = = 2 1 + 2 1 n = 1 ∑ ∞ 2 n n + 1 = 2 1 + 2 1 ( S 1 + S 0 ) = 2 1 + 2 1 ( S 1 + 1 ) Solving the resulting equation for S 1 we obtain that S 1 = 2 . In a similar way S 2 = 2 1 + n = 1 ∑ ∞ 2 n + 1 ( n + 1 ) 2 = = 2 1 + n = 1 ∑ ∞ 2 n + 1 n 2 + n = 1 ∑ ∞ 2 n + 1 2 n + n = 1 ∑ ∞ 2 n + 1 1 = = 2 1 + 2 1 S 2 + S 1 + 2 1 S 0 = 3 + 2 1 S 2 . Solving the resultant equation we get that S 2 = 6 .
Apparently we have not used Calculus, but for this algebraic method to work the series with sums S 0 , S 1 and S 2 must be convergent, and the corresponding proof requires the use of Calculus methods.
Remark : Notice that the term of the series corresponding to n = 0 is zero, and that is why we assume that the first value of n in the summation is 1 .
S ⟹ 2 1 S ⟹ S = n = 0 ∑ ∞ 2 n n 2 = n = 1 ∑ ∞ 2 n n 2 = n = 0 ∑ ∞ 2 n + 1 ( n + 1 ) 2 = n = 0 ∑ ∞ 2 n + 1 n 2 + 2 n + 1 = 2 1 n = 0 ∑ ∞ 2 n n 2 + n = 0 ∑ ∞ 2 n n + 2 1 n = 0 ∑ ∞ 2 n 1 = 2 1 S + n = 0 ∑ ∞ x d x d x n ∣ ∣ ∣ ∣ x = 2 1 + 2 1 ( 2 ) = x d x d n = 0 ∑ ∞ x n ∣ ∣ ∣ ∣ ∣ x = 2 1 + 1 = x d x d 1 − x 1 ∣ ∣ ∣ ∣ x = 2 1 + 1 = ( 1 − x ) 2 x ∣ ∣ ∣ ∣ x = 2 1 + 1 = 2 + 1 = 6
That's great! :D
Non calculus solution:
S = x + 4 x 2 + 9 x 3 + 1 6 x 4 . . .
Then S x = x 2 + 4 x 3 + 9 x 4 + 1 6 x 5 . . .
So S − S x = x + 3 x 2 + 5 x 3 + 7 x 3
Now, consider x + x 2 + x 3 + x 4 . . . = P P − x P = − 1 P = 1 − x 1 − 1
So, S ( 1 − x ) − P = 2 x 2 + 4 x 3 + 6 x 4 . . . = 2 ( x 2 + 2 x 3 + 3 x 4 . . . )
So now, x 2 + 2 x 3 + 3 x 4 . . . = a a x = x 3 + 2 x 4 + 3 x 5 . . . a − a x = x 2 + x 3 + x 4 + x 5 . . . = P − x
Therefore, S ( 1 − x ) − P = 2 a = 1 − x 2 ( P − x )
S = 1 − x 1 − x 2 ( P − x ) + P = 1 − x 1 − x 2 ( 1 − x 1 − 1 − x ) + 1 − x 1 − 1
If you are too lazy to simplify like me, just sub x = 0 . 5 to get 6 . Bye
Logic behind:
To show the logic I used, I'm just going to give a quick clue:
n 2 − ( n − 1 ) 2 = 2 n − 1 ⟹ S − S x 2 n − 1 + 1 = 2 n ⟹ S − S x − P 2 n − ( 2 n − 1 ) = 1 ⟹ a − a x = P − x
P=x+x^2+x^3+x^4+........
P/x=1+x+x^2+x^3+.....
P-P/x=1
P-P/x is not equal to x
Hint:: Try to genralise : n = 0 ∑ ∞ n 2 x n = ( 1 − x ) 3 x ( x + 1 )
Problem Loading...
Note Loading...
Set Loading...
n = 0 ∑ ∞ x n = 1 − x 1 Now differentiate the series (using the quotient rule - see bottom) and multiply by x to obtain n = 0 ∑ ∞ n x n = ( 1 − x ) 2 x Now repeat the previous step to obtain: n = 0 ∑ ∞ n 2 x n = ( 1 − x ) 3 x ( 1 + x ) Now let x = 2 1 ∴ n = 0 ∑ ∞ 2 n n 2 = 6 Quotient rule: y = v u ⟹ d x d y = v 2 v d x d u − u d x d v